Reseña de libro: BUTLER, Judith; FEMENÍAS, María Luisa; SAGOT, Montserrat; VALENCIA, Sayak; HALPERIN, David; RIBEIRO DOS SANTOS, Marinês (2023) Cartografías de género. CLACSO, Buenos Aires. Pp. 108 - Retana, Camilo (Espacio Abierto, 2023)
.